2020
DOI: 10.1532/hsf.2895
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Anterior Leaflet Pseudoprolapse Causing Severe Mitral Regurgitation and Its Ideal Surgical Procedure

Abstract: Background: The aim of this study is to evaluate severe mitral regurgitation caused by so called atrial leaflet “pseudoprolapse” and verify the effect of simple annular stabilization. Methods: One-hundred-twenty-two patients underwent surgery for severe mitral regurgitation at our institute between January 2015 to July 2018. Of those, 32 cases diagnosed as anterior leaflet prolapse that underwent mitral repair were analyzed. Ten cases with pseudoprolapse, which is defined as anterior leaflet prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Cumulatively, 366 (74%) patients had AF at the time the diagnosis of AFMR was made. Notably, nine studies had a 100% rate of AF in their cohorts, whereases Balogh et al 20 and Tanaka et al 13 reported AF in 93% and 60% of their patients, respectively. Four studies (33.3%) included information on prognostic scores such as the European System for Cardiac Operative Risk Evaluation II and the Society of Thoracic Surgeons Score.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Cumulatively, 366 (74%) patients had AF at the time the diagnosis of AFMR was made. Notably, nine studies had a 100% rate of AF in their cohorts, whereases Balogh et al 20 and Tanaka et al 13 reported AF in 93% and 60% of their patients, respectively. Four studies (33.3%) included information on prognostic scores such as the European System for Cardiac Operative Risk Evaluation II and the Society of Thoracic Surgeons Score.…”
Section: Resultsmentioning
confidence: 98%
“…Two studies (16.6%) identified a central MR jet as inclusion criteria, and one study (8.3%) considered Carpentier type 1 leaflet motion as inclusion criteria. Conversely, both Carpentier types 1 and 3 leaflet motion were excluded in Tanaka et al, 13 as well as Carpentier type 2 was excluded in the study by Matsumori et al 14 Interestingly, Tanaka et al 13 considered AFMR patients to be a subgroup of those affected by anterior leaflet pseudoprolapse rather than being a unique category, thus suggesting an overlap between the ways they defined these diseases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations